2018
DOI: 10.9778/cmajo.20180034
|View full text |Cite
|
Sign up to set email alerts
|

The top research questions asked by people with lived depression experience in Alberta: a survey

Abstract: epression is a major public health issue in Canada. 1 About 8% of adults aged 25-64 years are projected to experience major depression at some time in their lives. 2 Depression is estimated to account for at least $32.3 billion of direct and indirect costs to this nation annually. 3 Continued investment in research that explores prevention and treatment is needed, 4,5 in particular through engaging patients (i.e., people with depression, family members and informal caretakers) in this endeavour to better ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Involving patients and health care professionals in research has been shown to be a useful strategy for generating program development ideas and research priorities. 1116,19,20 The results of this study indicate that SSc patients and health care professionals have different but overlapping ideas for programs that would be useful to develop and for research questions they would like to see answered. Some of the most common suggestions for online programs are already being developed or tested by SPIN (e.g.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Involving patients and health care professionals in research has been shown to be a useful strategy for generating program development ideas and research priorities. 1116,19,20 The results of this study indicate that SSc patients and health care professionals have different but overlapping ideas for programs that would be useful to develop and for research questions they would like to see answered. Some of the most common suggestions for online programs are already being developed or tested by SPIN (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Online surveys have been used to identify patient research priorities in a range of medical conditions, including depression, 11 dementia, 12 prostate cancer, 13 asthma, 14 and kidney dialysis, 15 for example. Online surveys offer several advantages that build upon other strategies that SPIN has used, including the ability to collect data from large samples with a global reach, convenience for participants, time efficiency, low administrative costs, and the ability to incorporate diverse response formats within a single survey.…”
Section: Introductionmentioning
confidence: 99%
“…The final component, included in nearly all of the POR research thus far, is effectively translating the findings from the foundational scientists and PWLE to a larger audience that includes clinicians, other patients, and the wider community [26,27]. This is considerably more difficult than it seems at first glance, with questions such as what knowledge, to whom, by whom, and how the information should be distributed [28,29].…”
Section: Translational Researchmentioning
confidence: 99%
“…In Canada, the “Alberta Depression Research Priority Setting Project” asked clinicians and those with lived experience about the most important unanswered questions in depression research. Top priorities delineated include “Which treatment therapy or method is more successful for long term remission or recovery?”, “What are the long-term physical implications of pharmacotherapy for treating depression?”, and “For various treatment options … what are the advantages in terms of cost, effectiveness, relapse prevention and safety?”, alongside many others [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, treatment alone is unlikely to substantially reduce the prevalence and incidence of depression [ 13 ]; instead, a focus on prevention is necessary. Indeed, in a recent Alberta-based research project examining views from a range of mental health stakeholders, preventative measures were identified as a top priority for future depression research [ 14 , 15 ]. Preventing the occurrence or delaying the onset of depression can decrease symptoms [ 16 ] and reduce the burden for employers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%